Determinação de elementos potencialmente tóxicos em amostras de ovos e carapaças de tartarugas visando monitoramento ambiental - Etto, Pedro Vítor Gonçalez (Universidade Federal de São Carlos, 2023)
The development of society as we know it today requires investment in the exploitation of natural resources. A large part of Brazilian and international industry is dependent on raw materials such as iron, the most widely used and exploited metal in the world. To obtain minerals, however, it is necessary to prepare the site to be exploited, so the construction of dams for waste is essential. As these metals are not found in pure form and the transformation processes generate potentially toxic by-products, it is expected that the waste will be treated and kept away from living beings. However, this is not always respected, and this waste contaminates ecosystems, so physical or chemical methods are used to treat and identify the contaminants. This work aims to use ICP OES, an analytical technique, to identify and quantify potentially toxic elements in living organisms in order to carry out environmental monitoring. The results quantified the chemical elements of interest and point to possible contamination of the turtle species studied.
Determination of potentially toxic elements in samples of turtle eggs and shells for environmental monitoring
Keywords: Química analítica; ICP OES; Elementos tóxicos; Contaminação do ecossistema nacional; CIENCIAS EXATAS E DA TERRA::QUIMICA